Efficacy between 3-Dimensional and Champy Plates in Anterior Mandibular Fracture: 3-Dimensional and Champy Plates in Anterior Mandibular Fracture - Laghari, Bakhtawar; Kumar, Suneel; Khoso, Zeeshan; Rana, Hajra; Majeedano, Sajid Ali; Chandio, Benish (Pakistan Journal of Health Sciences, 2025)
Facial bone fractures or maxillofacial fractures are on the rise, specifically as a result of more road traffic accidents and sports incidents. The face is very sensitive both in terms of appearance and functionality; people who have been attacked in the face can have difficulty eating and speaking, or are extremely shy to socialize due to disfiguration. Objective: To compare the results of using the 3D mini plates in the treatment of the anterior mandibular fracture with Champy’s mini plates. Methods: A Quasi-experimental study was conducted at the Department of Oral and Maxillofacial Surgery of LUMHS Jamshoro, Pakistan, in six months, and the sampling technique used was non-probability convenience sampling. Data analysis was done using statistical software SPSS version 26.0. Results: At the end of six weeks, the results showed that the average surgical time that was taken in the surgical procedure was shorter in Group B than in Group A, being (50.94 ± 6.89) and (55.43 ± 3.24) respectively; F=16.44, p=0.001. Just as in Group B, the incidence of infection was considerably lower (8.6%) than in Group A, where it reached 28.6%, with all the differences being statistically significant (p=0.031). Conclusions: 3D plates provide a biomechanically stable and versatile solution to Champy’s mini plates. Because of the high strength of the material and corresponding flexibility, as well as ease of utilization, there is evidence that the 3D plates used in surgeries should be effectively employed in managing mandibular fractures.